2023
DOI: 10.7753/ijcatr1202.1004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Android-Based Learning as Interactive Learning Media in Reaction Rate Material on XI Class SMA Student

Abstract: This aims of this study are to: (1) find out whether android-based interactive learning media that developed have met the feasibility standards based on the android-based integrated BSNP, (2) find out whether student learning outcomes taught using android-based interactive learning media that have been developed higher than the Minimum Completeness Criteria (KKM) score on the reaction rate material. This research is a Research and Development with the ADDIE (Analysis, Design, Development, Implementation and Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…[8] Chemistry is difficult for students to understand because it is a subject that has facts, procedures, and concepts, and Chemistry is more than just solving problems; students must also learn descriptions such as chemical facts, chemical rules, and the material studied in chemistry is extensive. [9] A periodic table of elements is well-known in chemistry education. The periodic table of elements is a table that lists the names of chemical elements and categorizes them based on how similar their properties are.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Chemistry is difficult for students to understand because it is a subject that has facts, procedures, and concepts, and Chemistry is more than just solving problems; students must also learn descriptions such as chemical facts, chemical rules, and the material studied in chemistry is extensive. [9] A periodic table of elements is well-known in chemistry education. The periodic table of elements is a table that lists the names of chemical elements and categorizes them based on how similar their properties are.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data in Table 1 and Table 2, the needs analysis can be seen that the low interest and learning outcomes in chemistry can be caused by chemistry learning in schools not using appropriate learning media. The same thing was also conveyed by previous researchers who have succeeded in developing interactive learning media to teach reaction rates for XI Class SMA student (Silaban et al, 2023a).…”
Section: Define Stage To Need Assementmentioning
confidence: 52%
“…Similar results have also been reported in previous studies. The unlimited ability for students to open features will have a positive impact on increasing their interest in learning (Lubis and Ikhsan, 2015;Silaban et al, 2023a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related research can be found on the resend study, which concluded that in the chemistry learning process, teachers never use android-based learning media. As a result, Android-based interactive media is required in the learning process to improve students' comprehension [11] .…”
Section: Introductionmentioning
confidence: 99%